Analisis Pertumbuhan Ekonomi Kabupaten Pesisir Selatan Pendekatan Teori Solow - Murialti, Neng; Darwin, Ranti; Sandri, Siti Hanifa; Algusri, Jeki; Mufadel, Muhammad Alwi; Bakaruddin, Bakaruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
This study aims to analyze the effects of Gross Fixed Capital Formation (GFCF), employed population, average years of schooling, and internet use on economic growth in Pesisir Selatan Regency during the 2010–2025 period based on Solow growth theory. This study uses time series data obtained from BPS Pesisir Selatan Regency, BPS West Sumatra Province, and BPS Indonesia. The analytical method used is multiple linear regression. The results show that GFCF, employed population, average years of schooling, and internet use simultaneously have a significant effect on economic growth. Partially, GFCF has a positive but insignificant effect, while employed population and average years of schooling have positive and significant effects. Internet use has a negative and significant effect on economic growth. These findings emphasize the importance of improving human resource quality through education and strengthening digital literacy so that the internet can be used productively to support regional economic development.